Reduction Mechanisms of Copper, Cobalt and Iron during Low Temperature Recovery from Mineral Sulphide Concentrates - Yotamu Stephen Rainford Hara (The Minerals, Metals and Materials Society, 2013)
"The study focuses on the reduction mechanisms of copper, cobalt and iron during carbothermic reduction of copper-cobalt mineral sulphide concentrates in the presence of lime, in the temperature range of 1073K and 1273K. We have used three types of mineral concentrates which were derived from froth flotation from the Copperbelt region in Zambia. The reduction mechanisms were studied using thermogravimetric analysis in which selected reactions were stopped at different times for characterising the reaction mechanism using optical microscopy, XRD and SEM-EDX analyses. Using SEM-EDX analysis, we have analysed in details the stages of metallic phase formation during reduction process. Metallic cobalt and iron were embedded into copper, thereby permitting magnetic separation of the reduced metals even though copper is diamagnetic. Methods of preferential reduction of metal values were investigated by analysing the metallic phase formation.IntroductionIn conventional smelting or converting of copper sulphide minerals, metallic copper forms by giving off S02 gas on. Although in terms of overall energy balance the selective oxidation for metal production has major advantages, the process suffers from drawbacks in smelting complex concentrates containing copper, cobalt and iron sulphides minerals and these are: (i) cobalt and iron are oxidised, and consequently cobalt is lost into the slag phase. (ii) The volume of S02 gas produced is in low concentrations, which is insufficient for extracting sulphur or manufacturing sulphuric acid. The release of dilute S02 causes serious environmental pollution. The major cause for the loss of cobalt and iron into the slag, is due to that fact that the oxides of these metals are more stable than their sulphides. Since cobalt and copper are more valuable than iron, reducing conditions are required in a separate slag treatment reactor using electric arc melting for recovering the lost metal oxides from slag. This energy-intensive step makes metal making expensive.During chemical beneficiation of mineral sulphides (Cu2S, CoS, FeS) in the presence oflime (CaO), two types of equilibrium conditions may be set up either by forming CaS under reducing conditions, or by stabilizing CaS04 under oxidising conditions [l]. By comparison in the presence of carbon, CaS and metallic phases form, enabling the recovery of metals from sulphide minerals, which have been investigated by a number of authors [2-9]. During reduction of metal sulphide in the presence of lime and with carbon, it has been proven that the overall reaction le proceeds via two main steps: [5, 8, 9] (i) the anion exchange reaction between metal sulphides (MS) and CaO as shown in equation la, followed by (ii) the reduction of metal oxide (MO) via reaction lb."